Military Reform: Informal Military Power in Indonesian Politics After 1998 - Khairurrizqo, Khairurrizqo (Universitas Syiah Kuala, 2024)
Indonesia entered the era of political reform after the collapse of the Soeharto in 1998, which was marked by an agenda of government reform, including reform within the military. Reforms and dismantling of the dual-single doctrine (Dwifungsi) brought the army back to the barracks, and regulations ensured the army focused on its duties as guardians of national defense. Later in Indonesia's political process, informal military groups played a role behind the scenes as part of the team that formulated strategic policies. This research analyzes the development of military reform and influence in Indonesia from the reign of BJ Habibie to Joko Widodo and the factors that influenced the development of military reform. This paper uses a qualitative approach to describe the informal power of military groups in the political turmoil in Indonesia. This article uses data collection techniques in the form of documentation studies with a content analysis approach from various studies and news. The informal political power of the military group had a different impact on numerous policies of the President of Indonesia after the reformation. In the era of President BJ Habibie, the military still dominated, although the president later gave limits, especially to stop the Dwifungsi ABRI principle. In the Abdurrahman Wahid era, the influence of informal groups declined relatively due to Gus Dur's frontal policies to enforcing human rights. During the Megawati era, retired military officers strengthened the military's influence in Benny Moerdani's circle of influence. Under SBY, the influence of informal groups can be seen in his efforts to revoke TNI's business units entirely in various fields. The influence of informal groups returned in President Jokowi's era with his policy of recruiting retired military generals in various strategic posts in civilian ministries.